2021
DOI: 10.1111/jbl.12276
|View full text |Cite
|
Sign up to set email alerts
|

Managing extended supply chains

Abstract: We address how to manage extended supply chains that lie beyond the first‐tier suppliers. The first‐tier suppliers have their suppliers who provide them with goods or services. While lower‐tier suppliers are often not an explicit concern of the focal firm, the firm's performance not only depends on the performance of its first‐tier suppliers, but also on the performance of their suppliers and beyond. These lower‐tier suppliers are much less visible and may not even be known to the focal firm. Our intention is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…, 2022). But local SCs cannot take advantage of the market benefits of the globalized world, such as a diverse sourcing base (Choi et al. , 2021) or lower costs, which puts companies under high pressure to use their capacities efficiently in order to remain competitive (Shih, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2022). But local SCs cannot take advantage of the market benefits of the globalized world, such as a diverse sourcing base (Choi et al. , 2021) or lower costs, which puts companies under high pressure to use their capacities efficiently in order to remain competitive (Shih, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are risks associated with integration. A balance between domestic production and global trade will be critical for reducing uncertainty in the future and thus creating resilient supply networks (Choi et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This vital aspect of how transport is embedded in supply networks relates to Hesse and Rodrigue's (2004) notion that transport should not (only) be regarded as a derived demand but as an integrated demand. In addition, Choi et al. (2021, p. 201) found that part “of the complexity associated with supply chains is that buying firms do not necessarily know with certainty from where a supplier (first-tier or further upstream) is sourcing or sending the material”.…”
Section: Transport As Part Of Supply Networkmentioning
confidence: 99%
“…We are seeing this shift reflected in JBL submissions as well. The JBL articles published in 2021 reflect an evolving direction for L&SCM-one that focuses on strategic investments in technology (Dong & Franklin, 2021;Durach et al 2021;Kurpjuweit et al 2021;Sternberg et al 2021), the significance of managing a complex and changing global landscape (Choi et al 2021;Novak et al 2021;Wiedmer & Griffis, 2021;Wieland & Durach, 2021) and a shifting role of expectations and skill sets for L&SCM managers (Ellram & Tate, 2021;Falcone et al 2021). The current issue also reflects research that emphasizes the strategic nature of L&SCM and the value creation that comes as a result, as we highlight below.…”
mentioning
confidence: 97%